Taxonomic review and molecular phylogenetics of the reef gobiid genus Fusigobius from Taiwan with comments on a new species from South China Sea - Chen, I-Shiung; Chen, Kuan-Te; Yang, Yen-Cheng; Harefa, Tonisman; Chou, Li-Chin; Shen, Kang-Ning; Chang, Chih-Wei (Zootaxa, 2024)
A taxonomic review is given for the gobiid genus Fusigobius, known for its cryptic and inconspicuous body coloration, from the waters of Taiwan. Six species of Fusigobius have been formally confirmed from Taiwan, including four nominal species (F. duospilus, F. humeralis, F. inframaculatus, and F. neophytus), a newly recorded F. melacron, and a new species, Fusigobius taipinensis n. sp., recently collected from the South China Sea and southern Taiwan. The new species is morphologically close to F. duospilus, but can be clearly distinguished by several important coloration features on the first dorsal fin or body. Phylogenetic analysis and species delimitation inferred from partial sequences of the mtDNA ND5 gene support F. taipinensis as a valid discrete species and F. melacron as the plesiomorphic state for Fusigobius.